1994
DOI: 10.1021/j100062a005
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spectroscopy of CF3O in a Supersonic Jet: Symmetry and Rotational Structure of a Prototypical Perfluoroalkoxy Radical

Abstract: The A -2 electronic transition of CF3O was observed in a supersonic jet using laser-induced fluorescence.Rotational analysis of the high-resolution spectrum of the origin band is consistent with CF30 having C3" symmetry in both its ground and excited electronic states. The lowest level is best described as *E312 with residual unquenched electronic angular momentum, leading to a significant spin-arbit splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
11
1
Order By: Relevance
“…No features in experimental DF spectra can be assigned to the B̃ → à transition. This is different from primary and secondary alkoxy radicals, as well as the CF 3 O radical, for which both B̃ → X̃ and B̃ → à transitions were observed in DF spectra. In the present work, we resort to ab initio computations to predict the ÖX̃ separation (Δ E ÖX̃ ).…”
Section: Discussioncontrasting
confidence: 68%
“…No features in experimental DF spectra can be assigned to the B̃ → à transition. This is different from primary and secondary alkoxy radicals, as well as the CF 3 O radical, for which both B̃ → X̃ and B̃ → à transitions were observed in DF spectra. In the present work, we resort to ab initio computations to predict the ÖX̃ separation (Δ E ÖX̃ ).…”
Section: Discussioncontrasting
confidence: 68%
“…Later the IR band was also observed in another matrix isolation experiment [33]. Subsequently several laser-induced fluorescence [67][68][69][70] and dispersed fluorescence [69][70][71] spectra of CF 3 O radicals were recorded in the gas phase. From the analyses of laserinduced fluorescence excitation spectra of jet-cooled CF 3 O radicals, the origin of the A 2 A 1 X 2 E transition was found to begin at 28552 cm À1 and three fundamentals in the electronic excited state n 3 ¼ 635, n 5 ¼ 626, and n 6 ¼ 426 cm À1 have been detected [68].…”
Section: Cf 3 Omentioning
confidence: 96%
“…From the analyses of laserinduced fluorescence excitation spectra of jet-cooled CF 3 O radicals, the origin of the A 2 A 1 X 2 E transition was found to begin at 28552 cm À1 and three fundamentals in the electronic excited state n 3 ¼ 635, n 5 ¼ 626, and n 6 ¼ 426 cm À1 have been detected [68]. From the rotational fine structure of the transitions it was concluded that CF 3 O maintains C 3v symmetry in both the ground and excited state [67,68]. Five fundamentals, Jahn-Teller and spin-orbit coupling constants of high accuracy in the ground state have been determined from dispersed fluorescence spectroscopy on jet-cooled CF 3 O radicals [71].…”
Section: Cf 3 Omentioning
confidence: 97%
See 1 more Smart Citation
“…One possible approach to the dissociation dynamics in methoxy is to produce a unique C-H stretch motion by asymmetric deuteration to form CHD 2 O. The study of asymmetrically substituted methoxy radicals is also important from spectroscopic and quantum chemical points of view, since it is small enough to completely resolve the rotational and spin structure of both microwave and electronic spectra, and a rather complete analysis 10,20,21 has been reported for CH 3 O, 13 CH 3 O, and CD 3 O. Methoxy radicals with one or two deuterons have a nuclear symmetry corresponding to the MS group isomorphous with the C s rather than the C 3v point group, and the Jahn-Teller effect transforms into a pseudo Jahn-Teller effect. Efforts have been made in only a few cases, e.g., cyclopentadienyl 22 and methane cation 23,24 to analyze the rotational spectra of an asymmetric isotopologue of a Jahn-Teller molecule.…”
Section: Introductionmentioning
confidence: 99%